The Negative Impacts of Acromegaly on Bone Microstructure Not Fully Reversible - Duan, Lian; Yang, Shengmin; Wang, Lin Jie; Zhang, Yuelun; Li, Ran; Yang, Hongbo; Zhao, Yuxing; Du, Hanze; Zhai, Xiao; Gong, Fengying; Pan, Hui; Zhu, Huijuan; et al. (Frontiers in Endocrinology, 2021)
Purpose: This study aimed to evaluate the bone turnover markers and bone microarchitecture parameters derived from high-resolution peripheral quantitative computed tomography (HR-pQCT) in active and controlled acromegaly patients. Methods: This cross-sectional study involved fifty-five acromegaly patients from a tertiary hospital (23 males, 32 females, aged 45.0 ±11.6 years). Firstly, growth hormone (GH), insulin-like growth factor-1 (IGF-1) and markers for bone turnover were assessed. Next, we derived peripheral bone microstructure parameters and volumetric bone mineral density (vBMD) through HR-pQCT. These parameters were compared between acromegaly patients and 110 healthy controls, as well as between 27 active and 28 controlled acromegaly patients. Moreover, the relationship between GH/IGF-1 and bone microstructure parameters was analyzed through multiple linear regression. Results: As compared with healthy controls, acromegaly patients exhibited elevated cortical vBMD, reduced trabecular vBMD, and increased trabecular inhomogeneity in distal radius and tibia. While controlled acromegaly patients had slower bone turnover, they did not necessarily have better bone microstructure relative to active patients in inter-group comparison. Nevertheless, multiple regression indicated that higher IGF-1 was associated with lower tibial stiffness and failure load. Additionally, males with higher IGF-1 typically had larger trabecular separation, lower trabecular number, and larger cortical pores in radius. Moreover, patients with elevated GH typically had more porous cortical bone in radius and fewer trabeculae in tibia. However, the compromised bone strength in active patients was partially compensated by increased bone thickness. Furthermore, no significant linkage was observed between elevated GH/IGF-1 and the most important HR-pQCT parameters such trabecular volumetric bone density. Conclusion: Acromegaly adversely affected bone quality, even in controlled patients. As the deterioration in bone microstructure due to prolonged GH/IGF-1 exposure was not fully reversible, clinicians should be aware of the bone fragility of acromegaly patients even after they had achieved biochemical remission.